Organoleptic and Glycemic Response Tests of Sugar Palm Jam with Natural Sweeteners and Colorants - Dara, Widia; Yensasnidar; Dita Yuliarta; Leni Mursyidah Hasibuan; Muhammad Fathu Ridho (Universitas Airlangga, 2026)
Sugar palm fruit (kolang kaling) jam was developed using sugarcane (Saccharum officinarum) juice as a sweetener and dragon fruit (Hylocereus polyrhizus) peels as a natural dye. This study aimed to analyze the jam’s Macronutrient composition, organoleptic properties, glycemic index (GI) and glycemic load (GL). Two Jam formulations were tested through organoleptic assessment by 25 semi-trained panelists. The most preferred formula (4:1:2,4 ratio of sugarcane juice, dragon fruit peel, and sugar palm fruit) underwent proximate and glycemic analysis. The jam showed average liking scores of 6.22 (color), 5.52 (aroma), 6.14 (texture), and 6.12 (taste). It had a GI of 68.36 and GL of 17.09, both classified as medium. These findings suggest that sugar palm jam formulated with natural sweeteners and colorants might be suitable for consumption by individuals with diabetes mellitus type 2 in limited portions.